Inoculation for Neutralizing Misinformation: Replication of an Experiment on the Effect of the Fake Experts’ Strategy in Climate Change Communication’s Context - Abdalla, Joseph (AUC Knowledge Fountain, 2023)
Low acceptance of climate change and low support for its mitigation efforts can be due to public misconceptions towards climate change. Climate skeptics use a communication strategy of fake experts to spread misinformation through spokespersons who are not experts in the field. Inoculation can be a protective approach for tackling the misinformation’s effect. Previous research was conducted in the United States and Germany and was never conducted in Africa. This study aimed to complement the previous research findings with results for Egypt by replication an experiment by Cook et al. with a 2 × 2 between-subjects design. A total of 300 participants were recruited into the study and they were randomized into four stimuli groups (control, misinformation, inoculation, and inoculation + misinformation). A total of 274 eligible participants’ data was analyzed. The study explored climate change misinformation’s impact on the participants and tested an inoculation stimulus that could protect against misinformation pre-emptively. The effect of the difference in the participants’ demographics and the interactions with the study stimuli were also analyzed. The difference in the study stimuli had a significant effect on the participants for the perceived scientific consensus. The misinformation stimulus had a significant negative effect. The inoculation-only stimulus significantly neutralized the misinformation’s effect for both the perceived scientific consensus and the scientific consensus influence. The study also found that the differences in the sex, age, education level, and educational background of the participants had significant effects and significant interactions with the study’s stimuli on the study’s dependent variables.